Hubungan Antara Regulasi Diri Dengan Efikasi Diri Pengambilan Keputusan Karier Pada Siswa SMK Wikrama Bogor - Izdiharini, Kania; Cahyono, Rudi (Jurnal Syntax Fusion, 2023)
This research aims to determine the relationship between self-regulation and career decision-making self-efficacy among students at Wikrama Vocational School, Bogor. Vocational school graduates are the biggest contributor to the unemployment rate. One that influences. Vocational school education is provided to prepare students for the transition from school to the world of work. This research is quantitative research using a survey method distributed online. The research participants were 486 grade 12 students at Wikrama Vocational School, Bogor, aged 16-18 years. The measuring tools in this research used the Self-Regulation Questionnaire (SRQ) and Career Decision Self-Efficacy (CDSE). Data analysis used non-parametric statistical techniques with the Spearman's Rho correlation test technique. The results of the research analysis show that there is a significant positive relationship between self-regulation and career decision-making self-efficacy for Wikrama Bogor Vocational School students (r = 0.545; p = <0.001). So, the higher the self-regulation that Wikrama Bogor Vocational School students have, the higher the self-efficacy they have in making career decisions.